Evaluasi Pengelolaan Aset TI dengan IT Service Management pada PT PLN (Persero) UP3 Palembang - Innatsa Saffa Tarisha; Mulyati Mulyati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted to evaluate IT asset management using the IT Service Management approach at PT PLN (Persero) UP3 Palembang. This research focuses on the ITIL V3 framework with the service operation domain which includes service desk management, incident management, RACI, IT assets and networks. The results of this research show that although IT asset management is already at a fairly good maturity level with a maturity value at level 3